2017
DOI: 10.1002/ejp.1000
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity in new daily persistent headache: A cross‐sectional study

Abstract: Anxiety, depressive symptoms, somatization and pain catastrophizing were significantly more prevalent in new daily persistent headache when compared to healthy individuals and patients with chronic low back pain. Such effects should be sought for, as they might contribute to refractoriness to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
47
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 34 publications
(61 reference statements)
9
47
3
5
Order By: Relevance
“…Our study revealed a male predominance (female/male=0.9:1), which is nearly similar to data from India (0.8:1) [9] but contrary to data from the USA (2:1) [10]. The mean age at onset for NDPH is 26.7 years, which is similar to that reported by Uniyal et al (28.24 years) [9] (Table 5). The clinical characteristics of the NDPH in our study were bilateral localization, nonthrobbing nature, and a typical lack of association with nausea and vomiting; these characteristics were similar to those of chronic tension type headache in many cases.…”
Section: Clinical Features Of Ndphsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study revealed a male predominance (female/male=0.9:1), which is nearly similar to data from India (0.8:1) [9] but contrary to data from the USA (2:1) [10]. The mean age at onset for NDPH is 26.7 years, which is similar to that reported by Uniyal et al (28.24 years) [9] (Table 5). The clinical characteristics of the NDPH in our study were bilateral localization, nonthrobbing nature, and a typical lack of association with nausea and vomiting; these characteristics were similar to those of chronic tension type headache in many cases.…”
Section: Clinical Features Of Ndphsupporting
confidence: 88%
“…The clinical characteristics of the NDPH in our study were bilateral localization, nonthrobbing nature, and a typical lack of association with nausea and vomiting; these characteristics were similar to those of chronic tension type headache in many cases. However, other summarized literature demonstrated the presence of migraine-like features in NDPH patients, with a proportion of 35-64.1% (8,9,(11)(12)(13). NDPH typically occur in individuals without a prior headache history (1).…”
Section: Clinical Features Of Ndphmentioning
confidence: 99%
“…al 2009 [14]NorwayICHD 230,000 adult general population0.03% GPRobbins 2010 [15]USAM-ICHD271 NDPH51(72%)20(28%)2.58–76Cacausian:80.3%Black:5.6%Hispanic:9.9%Prakash 2012 [16]IndiaM-ICHD263 NDPH36(57%)27(43%)1.318–68Rozen 2016 [17]USAICHD-3β97 NDPH65(67%)32(33%)2Mea: F:32.4M:35.8Cacausian:98%Black:1%Hispanic:1%Uniyal et. al 2017 [18]IndiaICHD-3β55 NDPH45.5%54.5%0.8Mea: 28.24 S-L Silberstein-Lipton criteria, ICHD International classification of headache disorders, M-ICHD2 Modified ICHD2 (NDPH according to the criteria A and B of the ICHD-2 regardless of the presence of migraine features.) GP General population, CDH Chronic daily headache…”
Section: Methodsmentioning
confidence: 99%
“…[345] However, the phenomenon of somatization and pain catastrophization has largely remained less well studied in the area of headaches. [6] This is not unusual to see patients with chronic migraine also suffering from other pain and non-pain symptoms at different time points, thereby suggesting an existence of a relationship of migraine and somatic symptom disorder. Pain catastrophizing is another aspect of chronic pain that is not adequately studied.…”
mentioning
confidence: 99%
“…Pain catastrophizing is another aspect of chronic pain that is not adequately studied. Pain catastrophizing is the amplification of pain by negative thoughts that work through (a) exaggerated concern about negative consequences of pain or “magnification”, (b) repetitive thoughts about pain or “rumination”, (c) and a belief that nothing is going to change the pain or “helplessness.”[6] This is considered as one of the pathways of formation/consolidation of chronic pain circuits in the brain. Pain catastrophizing may also have role in making these chronic pains refractory to the treatment.…”
mentioning
confidence: 99%